2005
DOI: 10.1002/pola.21017
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: A naturally occurring long‐wavelength photosensitizer for diaryliodonium salts

Abstract: Curcumin, a naturally occurring, intensely yellow dye extracted from the spice turmeric, is an efficient photosensitizer for diaryliodonium salt photoinitiators at wavelengths ranging from 340 to 535 nm. With curcumin as a photosensitizer, it is possible to carry out the cationic photopolymerization of a wide variety of epoxide, oxetane, and vinyl monomers with long-wavelength UV and visible light. An example of the photopolymerization of an epoxide monomer with ambient solar irradiation is provided. Several o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(100 citation statements)
references
References 33 publications
1
99
0
Order By: Relevance
“…Our findings corroborate those of other studies aimed at reducing microbial activity by using PDT. 27,29,31,32,52 As the primary odontopathogen present in the supragingival plaque, S. mutans is closely related to enamel caries. Lactobacilli generally colonize after S. mutans have exposed the dentino-enamel interface, and they are often cultured from established carious lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings corroborate those of other studies aimed at reducing microbial activity by using PDT. 27,29,31,32,52 As the primary odontopathogen present in the supragingival plaque, S. mutans is closely related to enamel caries. Lactobacilli generally colonize after S. mutans have exposed the dentino-enamel interface, and they are often cultured from established carious lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The drug has a variety of traditional pharmaceutical applications, 31,32 including treatment of liver diseases, wounds, and inflamed joints, as well as for blood purification and microbial effects. 33 Curcumin has proven nontoxic in a number of cell cultures and animal studies.…”
mentioning
confidence: 99%
“…Polynuclear aromatic compounds are known 136,138,[149][150][151][152][153][154]185 to sensitize and consequently decompose onium salts via electron transfer in the exciplex (Scheme 17). We have recently demonstrated that similar photosensitization action can be achieved by highly conjugated thiophene derivatives such as 3,5-diphenyldithieno[3,2-b:2,3-d]thiophene (DDT).…”
Section: Cationic Polymerizationmentioning
confidence: 99%
“…It has some therapeutic effects on liver diseases, wounds, and inflamed joints, as well as for blood purification and microbial effects. 75 Curcumin has shown no toxic effects on a number of cell cultures and animal studies. It has a broad absorption peak in the 300-500 nm range (maximum 430 nm) and produces strong phototoxic effects.…”
Section: Curcuminmentioning
confidence: 99%